2002
DOI: 10.1046/j.1460-9592.2002.01605.x
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Risk Factors for Venous Obstruction After Implantation of Transvenous Pacing Leads

Abstract: Several investigators have shown that the incidence of venous obstruction after pacemaker implantation was observed in 31-50% of pacemaker patients. However, these previous reports did not investigate the venous system prior to implantation. The aim of this study was to determine the incidence and risk factors for venous obstruction in patients with transvenous pacing leads. The study included 131 consecutive patients (64 men, 67 women; mean age 71.3 +/- 9.8 years) who were investigated using intravenous digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(146 citation statements)
references
References 20 publications
5
130
1
5
Order By: Relevance
“…Surprisingly there was no clear influence of the implantation side in uni-or multivariate analyses which might be due to the rather small number of patients receiving right-sided device implantation. The only study published to date investigating the rate of venous obstruction both prior to as well as after implantation showed a significant increase in the occurrence of obstruction from 13.7 % to 32.9 % after implantation [10], which is comparable to our own results (11.0 % prior to implantation and 30.1 % prior to upgrade/revision). Overall venous obstruction (any grade of stenosis) was described in 25 -50 % of cases after ICD placement [3,14] and in 14 -64 % after pacemaker implantation [6, 7, 9, 10, 12], but to date no direct comparison of venous obstruction rates between pacemaker and ICD patients is available.…”
Section: Vessels 1033supporting
confidence: 87%
See 2 more Smart Citations
“…Surprisingly there was no clear influence of the implantation side in uni-or multivariate analyses which might be due to the rather small number of patients receiving right-sided device implantation. The only study published to date investigating the rate of venous obstruction both prior to as well as after implantation showed a significant increase in the occurrence of obstruction from 13.7 % to 32.9 % after implantation [10], which is comparable to our own results (11.0 % prior to implantation and 30.1 % prior to upgrade/revision). Overall venous obstruction (any grade of stenosis) was described in 25 -50 % of cases after ICD placement [3,14] and in 14 -64 % after pacemaker implantation [6, 7, 9, 10, 12], but to date no direct comparison of venous obstruction rates between pacemaker and ICD patients is available.…”
Section: Vessels 1033supporting
confidence: 87%
“…Therefore, the aim of the present study was to investigate the incidence of upper extremity venous obstruction, and to identify risk factors in a large patient population. Venographic studies investigating venous occlusion prior to device implantation in general found a prevalence of 4.4 -13.7 % [5, 10,18]. The occurrence of upper extremity deep vein thrombosis prior to any cardiac device implantation is often associated with malignancy and/or central venous lines.…”
Section: Risk Factors and Predictors For Venous Obstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous obstructions after transvenous implantation of electronic cardiac devices have been described as the commonest complication related to this approach [1][2][3][4][5][6][7][8][9][10][11][12], with ventricular dysfunction and the presence of temporary pacemakers ipsilateral to the implantation side being risk factors for its occurrence [6].…”
Section: Introductionmentioning
confidence: 99%
“…With the high risk of venous lesions, 3% to 10% of patients present with clinical manifestations, of which, deep venous thrombosis of the arms is the commonest complication [1][2][3][4][5][6][7][8][9][10][11][12]. Severe complications, such as pulmonary embolism and superior vena cava syndrome, with rates that vary between 0.6% and 5%, have been rarely described in the literature, [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%